STRATEGI PEMASARAN DALAM PERSAINGAN DUNIA USAHA - SUHANDI SUHANDI (LPPM STIA Banten, 2017)
Promotion is one way for companies to introduce their products. To carry out promotions with the right strategy, companies must take into account the amount of funds available and the amount of benefits obtained from the promotional activities carried out. In addition, the marketing strategy implemented must be reviewed and developed in accordance with market developments and the market environment. A company that is successful and able to maintain and increase its sales amidst its competitors is a company that has succeeded in determining its marketing strategy and competitive strategy appropriately. The determination of competitive strategy should be carried out by considering the size and position of each company in the market. Because large companies may be able to implement certain strategies that small companies clearly cannot. Vice versa. However, it is not uncommon for small companies with their own strategies to be able to generate the same or even better profit levels than large companies.